A combination of solid‐phase extraction and dispersive solid‐phase extraction effectively reduces the matrix interference in liquid chromatography–ultraviolet detection during pyraclostrobin analysis in perilla leaves. (23rd June 2015) - Farha, Waziha; Rahman, Md. Musfiqur; Abd El‐Aty, A. M.; Jung, Da‐I.; Kabir, Md. Humayun; Choi, Jeong‐Heui; Kim, Sung‐Woo; Jeong Im, So; Lee, Young‐Jun; Shin, Ho‐Chul; Kwon, Chan‐Hyeok; Son, Young‐Wook; et al.
Abstract Perilla leaves contain many interfering substances; thus, it is difficult to protect the analytes during identification and integration. Furthermore, increasing the amount of sample to lower the detection limit worsens the situation. To overcome this problem, we established a new method using a combination of solid‐phase extraction and dispersive solid‐phase extraction to analyze pyraclostrobin in perilla leaves by liquid chromatography with ultraviolet absorbance detection. The target compound was quantitated by external calibration with a good determination coefficient (R2 = 0.997). The method was validated (in triplicate) with three fortification levels, and 79.06– 89.10% of the target compound was recovered with a relative standard deviation <4. The limits of detection and quantification were 0.0033 and 0.01 mg/kg, respectively. The method was successfully applied to field samples collected from two different areas at Gwangju and Muan. The decline in the resiudue concentrations was best ascribed to a first‐order kinetic model with half‐lives of 5.7 and 4.6 days. The variation between the patterns was attributed to humidity. Copyright © 2015 John Wiley & Sons, Ltd.